Association between prehospital adrenaline administration and short-term outcomes in patients with shockable out-of-hospital cardiac arrest undergoing extracorporeal cardiopulmonary resuscitation: a propensity-score matched analysis - Shoji Kawakami; Hidenobu Koga; Tetsuhisa Yamada; Jun-Ichiro Nishi (International Journal of Cardiology: Heart & Vasculature)
Background: In patients with out-of-hospital cardiac arrest (OHCA) and an initial shockable rhythm undergoing extracorporeal resuscitation (ECPR), the effect of adrenaline on neurological outcomes remains uncertain. This study aimed to investigate the association between prehospital adrenaline and clinical outcomes in this patient population. Methods: This multicentre, prospective study (JAAM-OHCA registry) enrolled 81,234 patients with OHCA between 2014 and 2021. Patients with an initial shockable rhythm who underwent ECPR for a cardiac cause were eligible for this study. The primary outcome was a favourable neurological outcome at 30 days. The secondary outcome was prehospital return of spontaneous circulation (ROSC) or 30-day survival. A propensity score-matched analysis was performed to adjust for confounding and evaluate the independent association between prehospital adrenaline and study outcomes. Results: Among 1,061 patients, 442 (41.7 %) received prehospital adrenaline and 619 (58.3 %) did not. In 329 matched pairs, the prehospital ROSC rate was significantly higher in the adrenaline group (30 [9 %] vs 16 [5 %]; adjusted odds ratio [OR] 1.96, 95 % confidence interval [CI] 1.05–3.67, P = 0.03). However, 30-day survival (70 [21 %] vs 77 [23 %]; adjusted OR 0.88, 95 % CI 0.61–1.28, P = 0.51) and a favourable neurological outcome at 30 days (24 [7 %] vs 30 [9 %]; adjusted OR 0.78, 95 % CI 0.45–1.37, P = 0.39) were not significantly different. Conclusions: In patients with OHCA and an initial shockable rhythm who underwent ECPR, prehospital adrenaline was significantly associated with increased prehospital ROSC, but not with increased in survival and a favourable neurological outcome at 30 days.